Water quality and heavy metal analysis at tagal Moroli river of kampung Luanti in Ranau, Sabah - Mazlina Mizan (Universiti Malaysia Sabah press, 2024)
The Tagal system in Sabah has been adopted as a conservation strategy to address the depletion of freshwater fish populations. However, more research was needed on river water quality and physicochemical properties within the Tagal system. This study aims to assess the Water Quality Index (WQI) between Tagal (red zone) and non-Tagal (green zone) systems according to the National Water Quality Standard (NWQS) guideline of the Tagal Moroli River in the Ranau district of Sabah. Water samples were analysed (in-situ and ex-situ) four times at two-month intervals, with three sample stations within a 2 km radius distance from each other. The study revealed that water in the red zone (Tagal) was categorised as very clean (Class I) with the mean value for pH, dissolved oxygen, biological oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), ammoniacal nitrogen (AN) and heavy metals (Cu, Zn, Cd, Cr and As) with 8.09, 7.83 mg/L, 1 mg/L, 1.13 mg/L, 2.03 mg/L, 0.05 mg/L and all heavy metals was in natural levels respectively. The counterpart of rivers of the green zone showed similar traits and was classified as Class I. In conclusion, the Tagal system management positively impacts the Moroli River’s water quality, ensuring cleanliness and optimal condition. This improvement is largely due to local community efforts and strict regulations that reduce pollution, maintain natural flow, and support river health.